2017
DOI: 10.2147/dddt.s121122
|View full text |Cite
|
Sign up to set email alerts
|

Glycophenotype of breast and prostate cancer stem cells treated with thieno[2,3-<em>b</em>]pyridine anticancer compound

Abstract: Tumor progression may be driven by a small subpopulation of cancer stem cells (CSCs characterized by CD44+/CD24− phenotype). We investigated the influence of a newly developed thienopyridine anticancer compound (3-amino-5-oxo-N-naphthyl-5,6,7, 8-tetrahydrothieno[2,3-b]quinoline-2-carboxamide, 1) on the growth, survival and glycophenotype (CD15s and GM3 containing neuraminic acid substituted with acetyl residue, NeuAc) of breast and prostate cancer stem/progenitor-like cell population. MDA-MB-231 and Du-145 cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 42 publications
0
9
1
Order By: Relevance
“…1 ) was cytotoxic for both breast MDA-MB-231 and MDA-MB-453 cancer cells. In comparison to related 3-amino-5-oxo- N -naphthyl-5,6,7,8-tetrahydrotieno[2,3- b ]quinoline-2-carboxamide, reported earlier 2 , compound 1 was more cytotoxic. Halving of MDA-MB-231 cell viability was achieved with fivefold lower concentration after 4 h of treatment (5 µM compared to 25 µM).…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…1 ) was cytotoxic for both breast MDA-MB-231 and MDA-MB-453 cancer cells. In comparison to related 3-amino-5-oxo- N -naphthyl-5,6,7,8-tetrahydrotieno[2,3- b ]quinoline-2-carboxamide, reported earlier 2 , compound 1 was more cytotoxic. Halving of MDA-MB-231 cell viability was achieved with fivefold lower concentration after 4 h of treatment (5 µM compared to 25 µM).…”
Section: Discussioncontrasting
confidence: 57%
“…Recently, we described glycoconjugate GM3 and CD15s expression in MDA-MB-231 triple negative breast cancer stem cell subpopulation cultured with 3-amino-5-oxo- N -naphthyl-5,6,7,8-tetrahydrothieno[2,3- b ]quinoline-2-carboxamide, which was developed as a putative PLC inhibitor. A close structural analogue of 3-amino- N -(3-chloro-2-methylphenyl)-5-oxo-5,6,7,8-tetrahydrothieno[2,3- b ]quinoline-2-carboxamide, or compound 1 2 was chosen for this study due to its enhanced potency against the MDA-MB-231 cell line and its mechanism of action has been investigated 3 , 4 . Due to their ability to self-renew and to regenerate the primary tumour phenotypic heterogeneity, cancer stem cells are important therapeutical targets 5 .…”
Section: Introductionmentioning
confidence: 99%
“…As our initial work with thieno[2,3-b]pyridines and TDP1 was conducted with a relatively small library [35,38], we first carried out in vitro studies to validate thieno [2,3-b]pyridines as inhibitors of TDP1. One of our laboratories has synthesized and acquired [ 100 thieno [2,3b]pyridines derivatives [35,38,[69][70][71][72][73][74][75][76][77]. By using this extensive library, we screened for inhibition of TDP1 activity using a fluorescence-based inhibition assay with a synthetic oligonucleotide biosensor as substrate [78].…”
Section: Resultsmentioning
confidence: 99%
“…In our present study, apoptotic activity was tested on the previously mentioned Veronica species on MDA-MB-231 and the T24 cancer cell line. Mastelić et al [ 45 ] reported paclitaxel in a concentration of 40 nM (36.24 µg/mL) for apoptotic activity on the MDA-MB-231 cancer cell line. According to Mastelić et al [ 45 ], apoptotic activity of paclitaxel was 7.80% and for control, 1.58%, in apoptosis for the MDA-MB-231 cancer cell line.…”
Section: Discussionmentioning
confidence: 99%